Stress in ICU and non-ICU nurses - Keane, A; Ducette, J; Adler, D C (Nursing research (New York), 1985)
This study focused on the degree of burnout experienced by nurses in intensive care units and nonintensive care units. Nurses in both the surgical and medical ICUs, as well as nurses in the intermediate surgical and medical units and general surgical and medical units of a large, university hospital were the subjects. The data indicated that nurses in the ICUs did not differ in level of burnout from nurses in the other units. Across units, however, nurses who were characterized as more "hardy" experienced lower levels of burnout than nurses lower in this construct.